New Scheloribates (Acari, Oribatida, Scheloribatidae) from Ethiopia - Ermilov, Sergey G.; Rybalov, Leonid B.; Kuzmicheva, Evgeniya A. (Zootaxa, 2024)
Four new species of the genus Scheloribates (Oribatida, Scheloribatidae)—S. (Scheloribates) flexibilis Ermilov sp. nov., S. (S.) monosetosus Ermilov sp. nov., S. (S.) triangulus Ermilov sp. nov., S. (Topobates) tredecim Ermilov sp. nov.—are described, based on adults collected from litter in the afroalpine and bamboo locations in Ethiopia. Scheloribates (S.) flexibilis differs from the related species S. (S.) longisetosus by the length of aggenital, anal and adanal setae and the morphology of setal bothridial head and anterodorsal part of the leg tibia II. Scheloribates (S.) monosetosus differs from the related species S. (S.) concentricus by the length of anal and adanal setae and translamellar line, and the morphology of the setal bothridial head. Scheloribates (S.) triangulus differs from the related species S. (S.) monosetosus by the morphology of ventrodistal part of the leg femora II–IV, number of setae on the leg genu II, the length of the prolamella, and the development of the notogastral seta p1. Scheloribates (T.) tredecim differs from the related species S. (T.) scheloribatoides by the absence of the prolamella, distinctly longer aggenital, anal and adanal setae, and narrower body.